Diagnostic and correction of heterophoria - Drugović, Sonja; Synek, Svatopluk, 1951-; Masarykova univerzita. Katedra optometrie a ortoptiky (2017)
The presented master`s thesis describes the methods and principles of diagnostic and correction of heterophoria. In theoretical part I focus on metods examinating and measuring of heterophoria in optometry practice. There are show their possible solutions with prismatic correction. In practical part I meassuaring of heterophoria with using Madox teching and Von Grafee tests. The last chapter is focused on full correction of the measured heterophoria and treatment of heterophoria.
Vedoucí práce: Svatopluk Synek
Diplomová práce (Mgr.)--Masarykova univerzita, Lékařská fakulta, 2017
Keywords: heteroforie; heterophoria; strabismus -- diagnóza; Strabism; diplomové práce; master's theses